2019
DOI: 10.1016/j.celrep.2019.07.096
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone-Induced 3D Chromatin Reorganization Involves Active Enhancers Bound by Pipsqueak and Polycomb

Abstract: SUMMARYEvidence suggests that Polycomb (Pc) is present at chromatin loop anchors in Drosophila. Pc is recruited to DNA through interactions with the GAGA binding factors GAF and Pipsqueak (Psq). Using HiChIP in Drosophila cells, we find that the psq gene, which has diverse roles in development and tumorigenesis, encodes distinct isoforms with unanticipated roles in genome 3D architecture. The BR-C, ttk, and bab domain (BTB)-containing Psq isoform (PsqL) colocalizes genome-wide with known architectural proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 61 publications
2
42
0
Order By: Relevance
“…We found a complete absence of CP190 binding at the STARR-Seq peaks demonstrating that observed CP190-bound EcR sites are not the 20E-dependent enhancers. This result was in agreement with a recent study in Drosophila Kc cells, where CP190 binding was found at EcR sites which are not enriched with enhancer markers H3K9me1, H3K27Ac, and CBP 31 .…”
Section: Cp190 Is Present At Only a Portion Of Ecr-bound Sites In Thesupporting
confidence: 93%
See 1 more Smart Citation
“…We found a complete absence of CP190 binding at the STARR-Seq peaks demonstrating that observed CP190-bound EcR sites are not the 20E-dependent enhancers. This result was in agreement with a recent study in Drosophila Kc cells, where CP190 binding was found at EcR sites which are not enriched with enhancer markers H3K9me1, H3K27Ac, and CBP 31 .…”
Section: Cp190 Is Present At Only a Portion Of Ecr-bound Sites In Thesupporting
confidence: 93%
“…This is well correlated with a previous time-course analysis of CP190 binding in Kc cells (3-hour treatment with 20E), where it was shown that CP190 participates in stabilization of a basic regulatory hub at 20E-dependent genes in a hormone-independent manner 29 . The mode of CP190 action during 20E-dependent induction is likely to maintain a complex 3D structure at the loci enabling proper interactions between enhancers and promoters of genes, which appears to be transient and signal-dependent 31 . To illustrate all the possible ways of CP190 action at the 20E-dependent loci we provide a model of an average 20E-dependent gene (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S2C). We then tested if anchors of loops identified by SIP were enriched in proteins previously found to be important for looping in Drosophila (Eagen et al 2017;Ogiyama et al 2018;Gutierrez-Perez et al 2019). Indeed, Polycomb (Pc) and pipsqueak (Psq) are enriched on SIP loop anchors (Supplemental Fig.…”
Section: Sip and Sipmeta Allow Identification And Visualization Of Lomentioning
confidence: 99%
“…Psq is essential for oogenesis (Horowitz and Berg 1996), and it has been suggested to have a role as a repressor and in chromatin looping (Gutierrez-Perez et al 2019;Huang et al 2002).…”
Section: Introductionmentioning
confidence: 99%